Species composition, abundance and fishing methods of small-scale fisheries in the seagrass meadows of Gazi Bay, Kenya - Musembi, Peter; Fulanda, Bernerd; Kairo, James; Githaiga, Michael N. (Routledge, 2019)
Fisheries are important sources of livelihoods to coastal communities. In the tropics fishing is conducted from mangroves, seagrass meadows to coral reefs. Studies on fisheries in the tropics have focused on coral reef fisheries, with little attention to seagrass meadows and mangroves. Using creel survey and indepth interviews, this study assessed species composition, abundance and exploitation methods of fisheries from the seagrass meadows of Gazi Bay, Kenya. Eighty-five species were recorded with 8 species accounting for 75.7% of the total catch dominated by Leptoscarus vaigiensis, accounting for 30.9% of the total catch. Five dominant gears were observed: basket traps, hook and stick, handlines, nets and spear-guns. Basket traps were the most dominant accounting for 75.1% of the total catch by volume. These results underscore the value of the seagrass meadows to supporting fisheries. Gear management measures should be implemented for sustainability of the seagrass habitat and associated fisheries.
Keywords: Blue carbon; Seagrass meadows; Small-scale fisheries; Indian Ocean; food security; Kenya